Clinical Impact of Somatic Variants in Homologous Recombination Repair-Related Genes in Ovarian High-Grade Serous Carcinoma - Choi, Min Chul (Cancer Res Treat, 2020)
PURPOSE: In this study, we investigated the frequencies of mutations in DNA damage repair genes including BRCA1, BRCA2, homologous recombination genes and TP53 gene in ovarian high-grade serous carcinoma, alongside those of germline and somatic BRCA mutations, with the aim of improving the identification of patients suitable for treatment with poly(ADP-ribose) polymerase inhibitors. MATERIALS AND METHODS: Tissue samples from 77 Korean patients with ovarian high-grade serous carcinoma were subjected to next-generation sequencing. Pathogenic alterations of 38 DNA damage repair genes and TP53 gene and their relationships with patient survival were examined. Additionally, we analyzed BRCA germline variants in blood samples from 47 of the patients for comparison. RESULTS: BRCA1, BRCA2, and TP53 mutations were detected in 28.6%, 5.2%, and 80.5% of the 77 patients, respectively. Alterations in RAD50, ATR, MSH6, MSH2, and FANCA were also identified. At least one mutation in a DNA damage repair gene was detected in 40.3% of patients (31/77). Germline and somatic BRCA mutations were found in 20 of 47 patients (42.6%), and four patients had only somatic mutations without germline mutations (8.5%, 4/47). Patients with DNA damage repair gene alterations with or without TP53 mutation, exhibited better disease-free survival than those with TP53 mutation alone. CONCLUSION: DNA damage repair genes were mutated in 40.3% of patients with high-grade serous carcinoma, with somatic BRCA mutations in the absence of germline mutation in 8.5%. Somatic variant examination, along with germline testing of DNA damage repair genes, has potential to detect additional candidates for PARP inhibitor treatment.